Firalink: A bioinformatics pipeline for long non-coding RNA data analysis - Chauviere, Louis; Hoffbeck, Lucien; Shoaib, Muhammad; Tessier, Florent; Firat, Huseyin; Satagopam, Venkata; Devaux, Yvan (Non-coding RNA research, 2023)
The Firalink bioinformatics pipeline has been developed to analyse long non-coding RNA (lncRNA) data generated by targeted sequencing. This pipeline has been first implemented for use with the FIMICS panel containing 2906 lncRNAs useful for investigations in cardiovascular disease. It has been subsequently tested and validated using a panel of lncRNAs targeting brain disease. The pipeline can be adapted to other targeted sequencing panels or other transcriptomics data (e.g. whole transcriptome) through a change of the reference genome/panel. Therefore, Firalink can be applied to different lncRNA panels and transcriptomics data targeting multiple diseases. The Firalink pipeline works on Linux and is freely available to non-commercial users at https://gitlab.lcsb.uni.lu/covirna/covirna-ext/covirna-firalink-pipeline. Access will be granted after contacting bioinformatics@firalis.com. The pipeline is implemented with the Nextflow workflow manager using Python and R scripts. It will remain available for at least two years following publication and will be regularly updated and upgraded. For an example of the application of the Firalink pipeline using the FIMICS panel, see www.covirna.eu.